Therapeutic Targeting of Innate Immune Receptors Against SARS-CoV-2 Infection - Farooq, Mariya; Khan, Abdul Waheed; Ahmad, Bilal; Kim, Moon Suk; Choi, Sangdun (Frontiers in Pharmacology, 2022)
The innate immune system is the first line of host’s defense against invading pathogens. Multiple cellular sensors that detect viral components can induce innate antiviral immune responses. As a result, interferons and pro-inflammatory cytokines are produced which help in the elimination of invading viruses. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) belongs to Coronaviridae family, and has a single-stranded, positive-sense RNA genome. It can infect multiple hosts; in humans, it is responsible for the novel coronavirus disease 2019 (COVID-19). Successful, timely, and appropriate detection of SARS-CoV-2 can be very important for the early generation of the immune response. Several drugs that target the innate immune receptors as well as other signaling molecules generated during the innate immune response are currently being investigated in clinical trials. In this review, we summarized the current knowledge of the mechanisms underlying host sensing and innate immune responses against SARS-CoV-2 infection, as well as the role of innate immune receptors in terms of their therapeutic potential against SARS-CoV-2. Moreover, we discussed the drugs undergoing clinical trials and the FDA approved drugs against SARS-CoV-2. This review will help in understanding the interactions between SARS-CoV-2 and innate immune receptors and thus will point towards new dimensions for the development of new therapeutics, which can be beneficial in the current pandemic.